Study of alkali activated slag as alternative pavement binder. (20th October 2018) - Sun, Zengqing; Lin, Xiaochen; Liu, Pengfei; Wang, Dawei; Vollpracht, Anya; Oeser, Markus
Highlights: An alkali activated slag (AAS) was developed as alternative pavement binder. The AAS has similar compressive strength with cement but higher flexible strength. The AAS achieved comparable after-polishing skid resistance. The AAS mortar reduces CO2 emission to around 40% of cement counterpart. Abstract: The sustainable development of the building sector is an important concern of the public, industry and governments. One way to reduce the ecological footprint is to use building materials with less energy consumption and lower CO2 emissions. In this study, a clinker-free cementitious binder was synthesized through an alkali activation of ground granulated blast furnace slag. Flexural and compressive strength of the resulting alkali activated slag (AAS) were measured and compared with ordinary Portland cement (OPC). The Aachen Polishing Machine (APM) equipped with real vehicle tires and a British pendulum tester was applied to assess the skid resistance of AAS and OPC after polishing. Reaction products were documented using the X-ray Diffraction (XRD) technique to explore the reaction mechanism. In addition, the equivalent CO2 emission of AAS production was calculated to evaluate its environmental impact. Results show that the AAS possesses comparable after polishing skid resistance to OPC, but higher flexural strength and lower equivalent CO2 emission. All these demonstrate that AAS can be used as an environmentally friendly alternative binder for concrete pavement construction.